Diagnostic accuracy of strain imaging in predicting myocardial viability after an ST-elevation myocardial infarction. Issue 19 (May 2020) - Mghaieth Zghal, Fathia; Boudiche, Selim; Haboubi, Sofiane; Neji, Henda; Ben Halima, Manel; Rekik, Bassem; Mechri, Mehdi; Ouali, Sana; Hantous, Saoussen; Mourali, Mohamed Sami
Abstract : Abstract: In the acute phase of ST-elevation myocardial infarction (STEMI) viability imaging techniques are not validated and/or not available. This study aimed to evaluate the ability of strain parameters assessed in the acute phase of STEMI, to predict myocardial viability after revascularization. Thirty-one STEMI patients whose culprit coronary artery was recanalized and in whom baseline echocardiogram showed an akinesia in the infarcted area, were prospectively included. Bidimensional left ventricular global longitudinal strain (GLS), and territorial longitudinal strain (TLS) in the territory of the infarct related artery were obtained within 24 hours from admission. Delayed enhancement (DE) cardiac magnetic resonance imaging (CMR) was used as a reference test to assess post-revascularization myocardial viability. DE-CMR was performed 3 months after percutaneous coronary intervention. According to myocardial viability, patients were divided into 2 groups; CMR viable myocardium patients with more than half of infarcted segments having a DE <50% (group V) and CMR nonviable myocardium patients with half or more of the infarcted segments having a DE >50% (group NV). GLS and TLS were lower in group V compared to group NV (respectively: −14.4% ± 2.9% vs −10.9% ± 2.4%, P = .002 and −11.0 ± 4.1 vs −3.2 ± 3.1, P = .001). GLS was correlated with DE-CMR ( r = 0.54, P = .002) and a cut off value of −13.9% for GLS predicted viability with 86% sensitivity (Se) and 78% specificity (Sp). TLS showed the strongest correlation with DE-CMR ( r = 0.69, P < .001). A cut off value of −9.4% for TLS yielded a Se of 78% and a Sp of 95% to predict myocardial viability. GLS and TLS measured in the acute phase of STEMI predicted myocardial viability assessed by 3 months DE-CMR. They are prognostic indicators and they can be used to guide the priority and usefulness of percutaneous coronary intervention in these patients.